2015
DOI: 10.1186/s12893-015-0085-2
|View full text |Cite
|
Sign up to set email alerts
|

Bleeding complications in cholecystectomy: a register study of over 22 000 cholecystectomies in Finland

Abstract: BackgroundMajor bleeding is rare but among the most serious complications of laparoscopic surgery. Still very little is known on bleeding complications and related blood component use in laparoscopic cholecystectomy (LC). The aim of this study is to compare bleeding complications, transfusion rates and related costs between LC and open cholecystectomy (OC).MethodsData concerning LCs and OCs and related blood component use between 2002 and 2007 were collected from existing computerized medical records (Finnish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 26 publications
(43 reference statements)
0
7
1
1
Order By: Relevance
“…Bleeding in LC can be encountered intraoperatively or in the postoperative period. Intraoperative bleeding usually falls into one of the following four patterns: vessel injury, slippage of clips/ ligatures of the cystic artery, liver bed bleeding and miscellaneous [28]. However in our study in 44 (27%) patients were bleeding through gallbladder bed while in the study of Malik AM [29] reported in his study 11(1.05%) cases bleeding through gallbladder bed.…”
Section: Discussioncontrasting
confidence: 59%
“…Bleeding in LC can be encountered intraoperatively or in the postoperative period. Intraoperative bleeding usually falls into one of the following four patterns: vessel injury, slippage of clips/ ligatures of the cystic artery, liver bed bleeding and miscellaneous [28]. However in our study in 44 (27%) patients were bleeding through gallbladder bed while in the study of Malik AM [29] reported in his study 11(1.05%) cases bleeding through gallbladder bed.…”
Section: Discussioncontrasting
confidence: 59%
“…As for associated diseases, we opted for the use of SOI in the stratification of cases, since this score is what is usually reported in the literature [18][19][20] . The mean duration of our procedures was about 52 minutes, other works reporting values between 37 and 93 minutes in university hospitals [21][22][23][24][25][26][27][28] .…”
Section: Discussionmentioning
confidence: 62%
“…La CL no está exenta de riesgo de mortalidad vinculada al procedimiento. Pucher y colaboradores (3) reportan una mortalidad de 0,08%-0,14%, pero otros estudios reportan tasas de mortalidad hospitalaria de hasta 0,3%-0,7% (10,31) . Las causas de mortalidad pueden estar vinculadas a la inserción de trócares (lesión de grandes vasos, sepsis por lesión intestinal inadvertida), o a eventos intra o posoperatorios (lesión vascular del pedículo hepático, embolia gaseosa, descompensación cardiovascular, etc.).…”
Section: Discussionunclassified